ANALISIS SISTEM ANTRIAN PADA BANK SUMUT KCP USU MENGGUNAKAN MODEL ANTRIAN MULTI CHANNEL SINGLE PHASE: Queueing System Analysis At Sumut Bank KCP USU Using The Single-Phase Multi-Channel Queueing Model - Maulana, Putri Jehan; Citra, Indah Tribuana; Siregar, Anisa Hafizah; Siregar, R. Maisaroh Rezyekiyah (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2026)
The queuing system in the Customer Service (CS) department of Bank Sumut KCP USU was studied using the Multi Channel Single Phase (M/M/s) model. The purpose of this analysis was to evaluate service effectiveness and identify the best queueing arrangement to reduce customer waiting time. Direct observation of customer arrivals and service times over two working weeks produced primary data. The system was in a stable state. The results of the Chi-Square distribution test showed that service time followed an exponential distribution and customer arrivals followed a Poisson distribution. With one customer service officer, the service level increased to 6–8 customers per hour, compared to the usual customer arrival rate of 3–5 people per hour. The system is still stable, according to the agent workload level of 0.44, but efficiency decreases with an average waiting time of 12.5 minutes during peak hours (09:00–11:00). According to the simulation, waiting time can be reduced to less than one minute and the overall service duration to around nine minutes by adding one CS, making a total of two agents. Therefore, it is recommended that Bank Sumut KCP USU employ two active customer service agents during peak hours to improve customer satisfaction and service efficiency